PERFECTIONISM AND MINDFULNESS AS PREDICTORS OF ACADEMIC PROCRASTINATION: THE MEDIATING ROLE OF FEAR OF FAILURE IN VOCATIONAL HIGH SCHOOL STUDENTS - Dara, Yohana Lastri; Wahono, Puji; Adha, Maulana Amirul (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2025)
Academic procrastination is an interesting phenomenon that can negatively impact student performance. This study aims to analyze the influence of perfectionism and mindfulness on academic procrastination, mediated by fear of failure, in vocational high school students. This study uses a quantitative approach with a survey method. The population of this study was 206 students with a research sample of 136 people selected using purposive sampling technique. Data analysis was conducted using Partial Least Squares - Structural Equation Modeling (PLS-SEM) method using SmartPLS software. The results showed that perfectionism positively and significantly influenced Fear of Failure and academic procrastination. In contrast, Mindfulness negatively and significantly influences Fear of Failure and academic procrastination. Fear of Failure was also found to positively and significantly influence academic procrastination, as well as mediate the relationship between perfectionism and procrastination, and between Mindfulness and procrastination. The findings emphasize the need for psychological interventions to manage expectations and develop Mindfulness to reduce Fear of Failure and procrastination.